«BLENDED LEARNING» - THE ESSENCE AND FEATURES OF IMPLEMENTATION IN HIGHER EDUCATION - D. MITSENKO (Вісник: Київський інститут бізнесу та технологій, 2019)
The essence of the concept of "blended learning", its main features, varieties, stages of implementation and models of realization are considered in the article.